Application of Latvian illite clays in cosmetic products with sun protection ability (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Recent research shows that clay minerals can be used in sunscreens as UV filters instead of inorganic and organic compounds, which can cause unexpected photo-catalytic effect and damage the skin surface and can be absorbed into the skin and cause allergic reactions. In this study UV transmittance of suspensions containing clay fraction (mostly illite) and 50% glycerol/water solution was measured. Samples without chemical treatment, with removed carbonates and iron containing minerals (oxides and hydroxides) were analyzed. Results showed that the chemical treatment decreased UV protection ability. The highest increase of UV transmittance was observed for samples after removal of iron containing minerals. UV transmittance decreased by 10-14% when the concentration of clay fraction in the suspension was increased from 20 to 30 mass%.  Samples with the highest concentration of iron oxide showed also the highest UV protection ability.